Effect of Green Azolla (Azolla pinnata) supplementation on milk production, constituents and fatty acids profile in mid-lactating Barbari goats - Kumar, Ravindra; Abraham, G; Jaiswal, Pranta; Verma, Arun Kumar (Indian Journal of Dairy Science, 2022)
An experiment was conducted at Animal nutrition experimental unit, ICAR-Central Institute For Research on Goats, Makhdoom Farah, Mathura from Jan-March 2020 to study the effect of fresh azolla supplementation in lactating goats reared under intensive system. Twelve mid lactating Barbari goats were divided into two groups (CON and SUPP) of six each. CON was control (fed with 500 g concentrate pellets/head/day and ad libitum gram straw) while goats in SUPP was supplemented with 250 gram fresh azolla (20gDM) / day) along with gram straw and concentrate pellet. Body weight changes, milk production and milk constituents was studied. Milk production at 0, 30, 60 days of experimental feeding was recorded for two consecutive days. The animals were matured so no effect on body weight was observed. There was around 20% improvement in milk production at different stage of lactation on supplementation of 250g fresh azolla in mid lactating goats. There was no statistically significant (P